An Implementation of Error Minimization Position Estimate in Wireless Inertial Measurement Unit using Modification ZUPT - Darmawan, Adytia; Dewanto, Sanggar; Pramadihanto, Dadet (Politeknik Elektronika Negeri Surabaya (PENS), 2016)
Position estimation using WIMU (Wireless Inertial Measurement Unit) is one of emerging technology in the field of indoor positioning systems. WIMU can detect movement and does not depend on GPS signals. The position is then estimated using a modified ZUPT (Zero Velocity Update) method that was using Filter Magnitude Acceleration (FMA), Variance Magnitude Acceleration (VMA) and Angular Rate (AR) estimation. Performance of this method was justified on a six-legged robot navigation system. Experimental result shows that the combination of VMA-AR gives the best position estimation.